Asuhan Keperawatan Gerontik Pada Pasien Post FrakturDengan Pemberian Terapi Range Of MotionUntuk Meningkatkan Kekuatan Otot Di Panti Werdha Kasih Ayah BundaDi Kabupaten Tangerang - Febiola Dwi Puspitasari; Siti Robeatul Adawiyah; Rina Puspita Sari; Siti Rahayu (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2023)
Elderly is a process of experiencing anatomical, physiological and biochemical aging in organ tissues which can affect the state of function and ability of the body as a whole (Fatmah, 2019). In Indonesia, fracture cases are the third largest cause of death under coronary heart disease and tuberculosis. According to data compiled by Wrong Diagnosis (Ropyanto, et al, 2013), Indonesia is the largest country in Southeast Asia that experiences the most fractures of 1.3 million each year out of a population of around 238 million. In postoperative fracture patients, they experience delays in making movements due to muscle weakness and perceived pain (Ningsih, 2019). In an elderly person, it will bring about a complete change in his physique related to a decrease in the ability of the body's tissues, especially in physiological functions in the musculoskeletal system and the neurological system. One of the changes that occur in the elderly is a change in decreased muscle strength, the impact of decreased muscle strength is an increased risk of falling and causes walking to be less stable (Padila, 2020). Purpose: ROM is an exercise used to improve normal joint movement to increase muscle tone. Doing ROM exercises early can increase muscle strength so that it can stimulate more motor units involved, there will be an increase in muscle strength (Anggriani et al., 2020) Method: Using a muscle strength scale instrument. Conclusion: That Range Of Motion has benefits and is